2010
DOI: 10.1007/s11916-010-0161-3
|View full text |Cite
|
Sign up to set email alerts
|

Deep Brain Stimulation and Motor Cortical Stimulation for Neuropathic Pain

Abstract: Deep brain stimulation (DBS) is an important treatment option for neuropathic pain. DBS has a considerable history, and it can be used successfully for a wide number of pain syndromes. Epidural motor cortex stimulation (MCS) also is a treatment option for neuropathic pain. Less invasive than DBS, MCS has been rapidly adopted and studied since first described in 1991. A growing body of literature supports the use of MCS for facial pain, though further study to better define the mechanism of action and the most … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 36 publications
0
27
0
Order By: Relevance
“…Note that both montages present stimulation near the sensorimotor area lying inside the longitudinal fissure, but stronger for the feet motor area stimulation. This is a desired behaviour for feet motor area stimulation, since feet motor cortex is placed deep in the fissure, which makes it difficult to be targeted [64]. For both versions of the montage it should be considered that other nearby motor areas are affected, but not necessarily with significant effects.…”
Section: Resultsmentioning
confidence: 99%
“…Note that both montages present stimulation near the sensorimotor area lying inside the longitudinal fissure, but stronger for the feet motor area stimulation. This is a desired behaviour for feet motor area stimulation, since feet motor cortex is placed deep in the fissure, which makes it difficult to be targeted [64]. For both versions of the montage it should be considered that other nearby motor areas are affected, but not necessarily with significant effects.…”
Section: Resultsmentioning
confidence: 99%
“…ECS techniques have been reported in neuropathic pain [38], visual restoration, and tinnitus therapy [39]. Most interpretations suggest that enhanced neuroplasticity with more robust long-term learning and reorganization of neural circuits, possibly mediated by Gamma amino butyric acid (GABA)-ergic intracortical networks, may contribute to the improved neuronal functions associated with ECS [13].…”
Section: Discussionmentioning
confidence: 99%
“…Most interpretations suggest that enhanced neuroplasticity with more robust long-term learning and reorganization of neural circuits, possibly mediated by Gamma amino butyric acid (GABA)-ergic intracortical networks, may contribute to the improved neuronal functions associated with ECS [13]. It is believed that excitation of the motor cortex also results in inhibition of nociceptive neurons in somatosensory areas [38]. An implanted system should enhance efficacy and perhaps result in longer-term functional improvement [32].…”
Section: Discussionmentioning
confidence: 99%
“…A total of 73% (8/11) reported excellent pain control, which persisted unchanged in five patients (45%) for more than 2 years. Since then, various types of NP have been successfully treated with dural motor cortex stimulation (MCS), including post-stroke pain, spinal cord injury pain, thalamic pain, trigeminal neuralgia, trigeminal neuropathic pain, and trigeminal deafferentation pain (anesthesia dolorosa) syndromes 13. A recent meta-analysis of the various MCS trials found that 64% of patients with NP reported significant pain relief 14.…”
Section: The Development Of Brain Stimulation To Treat Chronic Painmentioning
confidence: 99%